Relaxation of photodarkening in SiO-As₂(S,Se)₃ composite layers - Indutnyi, I.Z.; Shepeliavyi, P.E.; Indutnyi, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Investigated in this work is the reversible photostimulated red absorption edge shift (photodarkening), ∆Eg, of As₂(S,Se)₃ nanoparticles embedded into the SiO matrix. As compared to continuous chalcogenide films, the remarkable ∆Eg increase (up to 4 times) with decreasing of chalcogenide particle sizes in composite SiO-As₂(S,Se)₃ layers was revealed. The exponential dependence of ∆Eg on storing time at different temperatures has been obtained. An activation energy of the transition of A₂2S₃ nanoparticles structure from a metastable photoexposed state to a ground annealed state is equal to 0.78 ± 0.06 eV. The effects are related to a spatial confinement of a photoexcited carrier diffusion length and an influence of particle sizes on intermediate-range order scale structure relaxation in the chalcogenide nanoparticles.